Mothers' Experiences in Caring for Stunted Toddlers: A Qualitative Study - Utario, Yossy; Mulyadi, Mulyadi; Kartika, Lia (IJNP (Indonesian Journal of Nursing Practices), 2024)
Background: Stunting is a condition characterized by the failure to thrive in toddlers, attributed to chronic malnutrition, resulting in shorter stature relative to their age. Mothers play a crucial role in the care of stunted toddlers.Objective: This study aimed to explore and describe the experiences of mothers in caring for stunted toddlers, employing a qualitative study with a phenomenological approach.Methods: The participants in this study comprised ten mothers serving as the primary caregivers for stunted toddlers aged between 19 and 36 years. Participants  were purposively selected, with criteria including being the primary caregiver and a willingness to participate. Data collection involved interviews and observations, and the analysis was then conducted using the Collaizi technique.Results: The findings of this study revealed six overarching themes: breastfeeding history, variations in complementary feeding, a spectrum of emotions experienced by mothers, wishes  for their children, the need for a robust support system, and barriers to feeding. Mothers' experiences in caring for stunted toddlers can provide valuable insights into their needs so that interventions can be designed to address the problems faced by other mothers of stunted toddlers.Conclusion: Mothers' experiences in caring for stunted toddlers can provide valuable insights into their needs so that interventions can be designed to address the problems faced by other mothers of stunted toddlers.